Results of the Field Stage in Third Year of Species and Provenances Trials of Paulownia Sieb.&Zucc. in Eastern Black Sea Region - Ulu, Fahrettin; Çetiner, Şaban; Eren, Necmettin; Ayan, Sezgin (My University, 2005)
Since it grows fast, suitable for agroforestry, has multi-purpose wood, leaves as feed of animals and useful flowers for bee-keeping, fertilise the soil, etc., Paulownia is an important fast growing tree. Turkish Ministry of Forestry has begun a project on Adaptation of Paulownia Species and Provenances in 1998, so has four trial sites in Eastern Black Sea Region. They are Samsun-Carsamba (20m), Ordu-Camsan (50m), OrduUlubey (900m) and Ordu-Golkoy (1400m) Seeds of 16 provenances of 3 Paulownia species (P.tomentosa, P.elongata, P.fortunei) and a hybrid (P.fortunei x tomentosa), which are imported from China, were sown in Trabzon-Of Forest Nursery in Spring 1999. In Fall 1999, 5 containerized seedlings (1/0 aged) were planted in each plot as 2 blocks, by Randomized blocks method. Torrent degraded the seedlings in Carsamba completely in June 2000. So, a new area was established in Spring 2002 in Samsun-Terme (30m). Survival and growth performance of the 3-aged seedlings in the field were discussed in this article. All seedlings of provenances and species of Paulownia in Golkoy (1400m) were died during the winter 1999. So, it may be said that similar high elevations and sites are not suitable for Paulownia.
Keywords: Paulownia, Species and provenances trials, Eastern Blacksea Region